Comparison of Posaconazole and Voriconazole Prophylaxis Following Induction Chemotherapy for Acute Myeloid Leukemia. (4th October 2017) - Bremmer, Derek; Patel, Monank; Moffa, Matthew; Walsh, Thomas
Abstract: Background: Acute myeloid leukemia (AML) is associated with a high incidence of invasive fungal infection (IFI). Both posaconazole and voriconazole have shown superiority in preventing IFI compared with fluconazole. However, limited data exists comparing posaconazole and voriconazole following AML induction. Methods: This Single-center retrospective cohort included all AML patients receiving induction chemotherapy at West Penn Hospital from September 1, 2013 to April 30, 2017 who received antifungal prophylaxis with either posaconazole delayed release (DR) or voriconazole. The primary composite outcome was incidence of proven, probable, or possible IFI or initiation of an alternative antifungal for treatment of suspected or proven IFI. Secondary outcomes include the duration of inpatient length of stay (LOS), all-cause 100-day mortality, duration of neutropenia, and incidence of re-induction. Results: The median duration of posaconazole and voriconazole was 18 and 20 days, respectively. There was no significant difference in the primary composite outcome between patients who received posaconazole or voriconazole (17% vs. 13%; P = 0.73). Baseline demographics and outcomes can be seen in Table 1. Conclusion: There were no differences in rates of IFI or other outcomes analyzed in our assessment of prophylactic posaconazole DR or voriconazole following AML induction chemotherapy. Disclosures: All authors: No reported disclosures.